Minerals levels in sugarcane syrup - VICENTINI-POLETTE, Carolina Medeiros; GALLO, Anderson de Souza; SILVA, João Henrique do Nascimento e; BERNARDI, Alberto Carlos de Campos; BORGES, Maria Teresa Mendes Ribeiro; VERRUMA-BERNARDI, Marta Regina (Food Science and Technology, 2024)
Sugarcane syrup derived from evaporating sugarcane juice serves as both a self-consumed product and a dietary supplement. It retains nutrients in sugarcane juice, especially minerals and nutritional compounds resistant to cooking processes. This study evaluated the mineral content of Brazilian sugarcane syrup by using Inductively Coupled Plasma Optical Emission Spectrometry. The syrup was found to have high concentrations of potassium, magnesium, calcium, and phosphorus (340, 57, 49, and 48 mg 100 g-1, respectively). Although the qualitative mineral composition of the evaluated products was relevant and consistent, there was considerable quantitative variation; therefore, standardization based on a narrow range of acceptable values is not recommended. It would take 243-1157 g of syrup to replace 200 g of whole cow’s milk. Nonetheless, sugarcane syrup contains essential minerals with proven health benefits. Potassium had the highest average concentration (up to 781.53 mg 100 g-1), followed by magnesium (10.82-94.69 mg 100 g-1), with iron ranking fifth (8.82 mg 100 g-1). Despite the quantitative variation, the qualitative mineral composition remained relevant. Therefore, a narrow standardization based on a limited range of values is not recommended. Nonetheless, sugarcane syrups with lower mineral levels can be considered nutritionally adequate.